Treatment of Maxillary Second Premolar with 4 Roots - Z. Allahem; S. AlYami (Hindawi Limited, 2020)
Aim. To report a case of maxillary second premolar with four roots and four separate foramina and the use of CBCT to help identify the root canal system configuration. Summary. A 45-year-old female patient with a no significant medical history was referred for treatment tooth #15. The tooth was diagnosed with symptomatic irreversible pulpitis and symptomatic apical periodontitis. After taking periapical radiographs and expected uncommon morphology, CBCT was taken to help confirm canals configuration and aid in the treatment of the case. Root canals treatment was carried without complication under dental operating microscope using a rotary system and continuous wave obturation.